PARTISIPASI MASYARAKAT DALAM MENANGGULAGI BANJIR DAN ROB DI KAWASAN TAMBAK REJO SEMARANG TAHUN 2018 - Raga Nur Aditya Ramadhan; Dewi Erowati (Journal of Politic and Government Studies, 2019)
The purpose of this study was first to analyze community participation in tackling floods and the Tambakrejo area, and the second to analyze what obstacles were faced inovercoming the Tambakrejo area.The results showed that community participation in the handling of floods was very real, especially in listening to the emergency situation, but flooding caused additional regional financial burdens and surrounding communities, especially to rehabilitate and heal pre-damage community functions. The occurrence of flooding is relatively short and repetitive per year, the people copying are ready for further disasters and there are moreefforts to anticipate this, so that losses can be minimized. The implications of environmental care in handling natural disasters in the form of floods in Kampung Tambakrejo include seven interaction mechanisms, namely: (1) deduction (resistance); (2) information transfer (information sharing); (3) consultation (commitment not by consultation); (4) consensus andintake of agreement with; (5) collaboration; (6) enabling the absence of risk sharing (sharing risk-empowerment); (7) partnering and enabling (partnership and empowerment).Keyword: Community Participation, Flood Mitigation, Rob Tambakrejo